Living Qur’an and Hadith in Cultivating Morals of Early Childhood: A Case Study of Nussa Animation Film Episode ‘Please and Thank You’ - Risma Rahatuningtyas; N. Siti Sopiah; Muhamad Rafi Anggara; Pidi Mohammad Setiadi (Islamic Research, 2022)
This article examines the living Qur'an and hadith in cultivating early childhood morals, especially in the Nussa animation film episode Please and Thank You. This study aims to determine the role of the Nussa animation film on the character and morals of early childhood in the era of globalization. This research used a quantitative approach through cluster sampling data collection methods as many as 30 respondents conducted at SDN 1 Sukaraja and SDN 2 Cinangka with age criteria 7-8 years. The results found that correlation between the Nussa animation film against early childhood morals was 34% and has an effect of 11.6%. The transmission process presented in the Nussa animation film occurs through Umma's character as a parent and a quote at the end of the story. The wisdom contained in the Nussa animation film is in accordance with the hadith narrated by Al-Baihaqi, namely that the Messenger of Allah was sent to improve human morals and the Qur'an Surah Ali-Imran verse 110 which explains the importance of good behavior towards others as a reflection of the behavior of a Muslim and the best of the people. Umma’s character convey messages from the content of the Hadith of Al-Baihaqi and the Qur'an Surah Ali-Imran verse 110 history which is explained implicitly. So, it can be concluded that the morals of students at SDN 1 Sukaraja and SDN 2 Cinangka are not influenced by the viewing of the Nussa animation film.